2017
DOI: 10.1158/1541-7786.mcr-16-0260
|View full text |Cite
|
Sign up to set email alerts
|

ECM Composition and Rheology Regulate Growth, Motility, and Response to Photodynamic Therapy in 3D Models of Pancreatic Ductal Adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is characterized by prominent stromal involvement, which plays complex roles in regulating tumor growth and therapeutic response. The extracellular matrix (ECM)-rich PDAC stroma has been implicated as a barrier to drug penetration, though stromal depletion strategies have had mixed clinical success. It remains less clear how interactions with ECM, acting as a biophysical regulator of phenotype, not only a barrier to drug perfusion, regulate susceptibilities and resistanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 47 publications
2
35
0
Order By: Relevance
“…In the present study, we specifically leverage the capability to manipulate ECM rheology via photocrosslinking as a means to study how activation of invasive behavior impacts upon responsiveness to chemotherapy and photodynamic therapy (PDT). This line of investigation is motivated by our previous study using transplanted 3D pancreatic tumor spheroids in collagen and laminin‐rich ECM which promote and constrain, respectively, the invasive progression of peripheral cells of the primary spheroid into surrounding ECM . We found that ECM‐infiltrating cells exhibit increased sensitivity to PDT, yet decreased response to chemo, which is also consistent with evidence of increased epithelial–mesenchymal transition (EMT) in invading cells.…”
Section: Introductionsupporting
confidence: 75%
“…In the present study, we specifically leverage the capability to manipulate ECM rheology via photocrosslinking as a means to study how activation of invasive behavior impacts upon responsiveness to chemotherapy and photodynamic therapy (PDT). This line of investigation is motivated by our previous study using transplanted 3D pancreatic tumor spheroids in collagen and laminin‐rich ECM which promote and constrain, respectively, the invasive progression of peripheral cells of the primary spheroid into surrounding ECM . We found that ECM‐infiltrating cells exhibit increased sensitivity to PDT, yet decreased response to chemo, which is also consistent with evidence of increased epithelial–mesenchymal transition (EMT) in invading cells.…”
Section: Introductionsupporting
confidence: 75%
“…An increasing body of evidence suggests that the tumor microenvironment has a profound impact on cancer progression and therapeutic responses (1)(2)(3)(4). Extracellular matrix (ECM), a major component of the microenvironment, is composed of a combination of macromolecules (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these results demonstrate that EGFR inhibition sensitizes MPM cells to PDT‐mediated apoptosis even with the addition of cell–cell and cell–matrix interactions, suggesting that this may be a potentially effective way to improve outcomes in patients undergoing eP/D‐pPDT. After attempting multiple potential methods of 3D culture for these MPM cell lines, we determined that Matrigel overlay was most effective and relevant to the defined experimental questions and found that MPM cells grow similarly to breast, ovarian, and pancreatic tumor cell lines in Matrigel . If larger 3D cultures are desired, Broaddus et al .…”
Section: Discussionmentioning
confidence: 99%
“…Compared to monolayer cultures, when MPM cells are grown as nonadherent spheroids in the absence of artificial ECM, they upregulate genes associated with the immune response and lymphocyte/cytokine stimulation while downregulating apoptosis-related genes (35). Survival signaling (including EGFR) and invasive behavior of cancer cells in the presence of ECM basement membrane also differs significantly from monolayer (36,37) and is often altered depending on the biochemical and biophysical properties of the ECM in contact with cells (25,38). Here, we found that, regardless of the biophysical composition of the ECM, EMP mesothelioma cells had increased phospho-EGFR after PDT (Fig.…”
Section: Discussionmentioning
confidence: 99%